2001
DOI: 10.1080/00140130120297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic office chairs on trunk kinematics, trunk extensor EMG and spinal shrinkage

Abstract: To cite this Article van DieËn, J. H. , De Looze, M. P. and Hermans, V. (2001) 'Effects of dynamic office chairs on trunk kinematics, trunk extensor EMG and spinal shrinkage ', Ergonomics, 44: 7,[739][740][741][742][743][744][745][746][747][748][749][750] To link to this Article: DOI: 10.1080/00140130120297 URL: http://dx.doi.org/10.1080/00140130120297Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
107
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(117 citation statements)
references
References 23 publications
6
107
1
3
Order By: Relevance
“…Chronic low back pain (LBP) is one such musculoskeletal disorder that is commonplace, with almost everyone experiencing it at one time or the other [4]. Prolonged periods of sitting hinder or restrict the movement of the lower spine and, therefore, prevent changes in the hydrostatic pressure in the intervertebral discs and seem to be detrimental for nutrition of the vertebral disc [57]. Krämer [8] reported that periodic changes in the loads of the intervertebral discs are critically important for not only their nutrition but also resistance against pathological changes, since frequent changes between high and low disc loads are able to induce an effective pump mechanism in the vertebral discs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic low back pain (LBP) is one such musculoskeletal disorder that is commonplace, with almost everyone experiencing it at one time or the other [4]. Prolonged periods of sitting hinder or restrict the movement of the lower spine and, therefore, prevent changes in the hydrostatic pressure in the intervertebral discs and seem to be detrimental for nutrition of the vertebral disc [57]. Krämer [8] reported that periodic changes in the loads of the intervertebral discs are critically important for not only their nutrition but also resistance against pathological changes, since frequent changes between high and low disc loads are able to induce an effective pump mechanism in the vertebral discs [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Graf et al (1995), a good chair would therefore be a chair that supports the body in a variety of desirable positions. There is also an indication that sitting in a non-static chair (backrest and seat pan follow the human body movements) is better for the back load (Dieën et al, 2001) compared with sitting in a static chair (fixed seat pan and backrest).…”
Section: Introductionmentioning
confidence: 99%
“…The sitting behavior analysis becomes an important research topic recently in a variety of domains, such as biomedical engineering, public healthcare service and facility design. It has been suggested that poor sitting behaviour can cause a threat to human body by linking to various pains and other complications [1,2]. Previous studies have showed that some common sitting postures of human body can lead to lumbar flexion and higher compressive forces in lumbar joints [2,3].…”
Section: Introductionmentioning
confidence: 99%